(untitled) (Scientific journal of the Fergana State University, 2023)
At the end of the 19th century and at the beginning of the 20th century, the tradition of Zullisonayn reached a new level. In the same period, there was a period of changes in literature, literally, renewal. Because by this time, jadidism had appeared as a very broad and active movement in social life. This had a direct impact on literature. In our article, we tried to shed light on the new image of this evolution ad the new interpretation of the Zullisonayn tradition.